Multiscale analysis of eusocial trafﬁc dynamics - Quiroga, Gladys Julieth Castiblanco (2020)
Different from human trafﬁc, the trafﬁc of social insects seems highly smooth and stable. Here, we tested the trafﬁc stability of Constrictotermes cyphergaster aiming to know the causes behind their smooth trafﬁc. Our results indicate that the patterns formed at the colony level (the macro- scopic scale) are a consequence of inter-individual interactions (the micro- scopic scale). In particular, our ﬁndings indicate that the stability of ter- mites’ trafﬁc is a consequence of the coordinated (co-operative) movements which emerge from inhibitory interindividual interactions. In addition, we showed that an inverse cycle of light, temperature, and relative humidity can reset the foraging rhythm of nocturnal open-forager termites. Our pro- tocol was highly effective to induce foraging during the day. Keywords: Forraging. Trafﬁc dynamics. Termites